Integrating environment characterestics and fisheries management in galas river basin - Hashim, Rohasliney (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
River fisheries conbibute significantly to the food security, health and livelihoods of hundreds of millions of people. Currently, river and floodplain fisheries In Asia are yielding an estimated 16 million tons annually worldwide. However, as use of water for lrrlgatlon has Increased, together with demand for urban and lndUstrlal use, fish catches along these river systems have declined. Kelantan recorded more than 35 freshwater species to date. It Is estimated that river fish landings In Kelantan only contilbuted about 3.5 to 4.1 'M> of total river fisll production. This contribution has been considered as the optimum level and It Is expec:ted to be In the region of 87,000 kg per year, occasionally fluctuated depending on the sitnation. Galas River Basin (GRB)'s case study revealed that GRB is contributed about 15-20 % of total river fish production In Kelantan (average 21, 432 kg of two year sampling. 2008-2009). Total CPUE (g/hour/yr) showed that GRB Is prodndng a very low catch if compared to other Inland fisheries. Fish biomass and CPUE did not have a slgn!Rcant; correlation with water quality because water quality did not fluctuate to a great extent during sampling periods and acceptable for fish growth and survival Study had been conducted In Galas River because It Is one of prominent river conbibutlng Into Ke1antan River In Kelantan State. Intensive sampling actlvtties were carried out twice In a year which encompass rainy and dry season. Sampling was carried out In two years for better results and analysis.